2020
DOI: 10.1038/s41598-020-78177-6
|View full text |Cite
|
Sign up to set email alerts
|

Dissipation kinetics and biological degradation by yeast and dietary risk assessment of fluxapyroxad in apples

Abstract: The aim of this study was to investigate the dissipation kinetics of fluxapyroxad in apples, the influence of biological treatment with yeast, and the estimation of dietary exposure for consumers, both adults and children. The gas chromatography technique with the electron capture detector was used to analyse the fluxapyroxad residues. Samples of apples were prepared by the quick, easy, cheap, effective, rugged and safe (QuEChERS) method. The average fluxapyroxad recoveries in apple samples ranged from 107.9 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…In HP, we expected intense oxidizing effects [25,26], and in PBC, we expected an alkaline hydrolysis effect [27,28]. With the use of LDC detergent, we washed the a.s. away without disintegration effects [28,29], and in microbes, we expected an active disintegration of residues, which can serve the microbes as a source of nutrients [30,31]. In all four LRPs, we influenced the pH values on the fruit surfaces and also the solubility of surface deposits.…”
Section: Discussion On Effects Of Applied Preparations On Pesticide R...mentioning
confidence: 95%
See 1 more Smart Citation
“…In HP, we expected intense oxidizing effects [25,26], and in PBC, we expected an alkaline hydrolysis effect [27,28]. With the use of LDC detergent, we washed the a.s. away without disintegration effects [28,29], and in microbes, we expected an active disintegration of residues, which can serve the microbes as a source of nutrients [30,31]. In all four LRPs, we influenced the pH values on the fruit surfaces and also the solubility of surface deposits.…”
Section: Discussion On Effects Of Applied Preparations On Pesticide R...mentioning
confidence: 95%
“…Microbes can be considered as a relevant factor. For example, in some studies [31], it was shown how efficient yeast-based preparation and bacteria-(Bacillus) and fungi (Trichoderma)-based products can be useful in the degradation of residues of fluxapyroxad (by yeasts) and penthiopyrad (by fungi) deposited on the surface of apples. We think that the microbes have potential as a preharvest treatment to reduce pesticide residues; this is a neglected and underestimated approach to cope with residue problems.…”
Section: Discussion On Effects Of Applied Preparations On Pesticide R...mentioning
confidence: 99%
“…Fungi have been reported to degrade a wide range of different pesticides, including organochlorines, organophosphorus compounds, pyrethroids, and carbamates (Maqbool et al, 2016;Bokade et al, 2021;Bose et al, 2021;Kumar et al, 2021); for example Lindane (Dritsa et al, 2009), Endosulfan (Bhalerao and Puranik, 2007), DDT (Purnomo et al, 2010), Atrazine (Bastos and Magan, 2009;Goncalves et al, 2012), Dieldrin and Aldrin (Xiao et al, 2011), among others. In some cases, specific fungi are even suggested as candidates to degrade fungicides, such as broad-spectrum pyrazole-carboxamide fluxapyroxad (Podbielska et al, 2020), which is often applied to counteract fungal diseases of apple trees (He et al, 2016). Just as the term 'pesticide' encompasses a wider range of different compounds, degradation of these is not confined to one fungal taxon.…”
Section: Degradation Of Pesticidesmentioning
confidence: 99%